Pengaruh Kualitas Layanan, Kepercayaan, Dan Komitmen Terhadap Loyalitas Nasabah Pada Bank Syariah Mandiri Kantor Cabang Pembantu Ulak Karang Padang. - Sutiyem Sutiyem; Tika Arinda Fitri (JURNAL PUNDI, 2021)
This study aims to (1) determine the effect of service quality on customer loyalty at Bank Syariah Mandiri Ulak Karang Padang Sub-Branch Office, (2) To determine the effect of trust on customer loyalty at Bank Syariah Mandiri Ulak Karang Padang Sub-Branch Office., (3) ) To determine the effect of commitment on customer loyalty at Bank Syariah Mandiri Ulak Karang Padang Sub Branch Office, (4) To determine the effect of service quality, trust, and commitment to customer loyalty at Bank Syariah Mandiri Ulak Karang Padang Sub Branch Office. The variables used in this study are service quality, trustworthiness, and commitment as independent variables and customer loyalty as the dependent variable.This type of research is quantitative research, with descriptive causal. The sampling technique used purposive sampling. The number of samples used is 100 samples who are customers of Bank Syariah Mandiri Ulak Karang Padang Sub-Branch Office.The results of this study indicate that service quality, trust, and commitment have a positive and significant effect on customer loyalty. The adjusted R2 value is 0.814, then the contribution of the influence of service quality, trust, and commitment to customer loyalty is 81.4% and 18.6% is influenced by other variables not examined in this study. This means that the three variables need to be considered and considered by the company.